2004
DOI: 10.1128/iai.72.7.4004-4009.2004
|View full text |Cite
|
Sign up to set email alerts
|

Yersinia enterocolitica Type III Secretion Depends on the Proton Motive Force but Not on the Flagellar Motor Components MotA and MotB

Abstract: The flagellum is believed to be the common ancestor of all type III secretion systems (TTSSs). In Yersinia enterocolitica, expression of the flagellar TTSS and the Ysc (Yop secretion) TTSS are inversely regulated. We therefore hypothesized that the Ysc TTSS may adopt flagellar motor components in order to use the pathogenicity-related translocon in a drill-like manner. As a prerequisite for this hypothesis, we first tested a requirement for the proton motive force by both systems using the protonophore carbony… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
94
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 34 publications
8
94
0
Order By: Relevance
“…Our conclusions are consistent with previous observations of a PMF requirement for flagellar growth from more than 25 years ago 19 , and extend the earlier findings in showing that export can be energized by PMF alone in the absence of any type III secretion ATPase 7 . Use of the proton gradient is perhaps not surprising given the speed of type III secretion and the likely advantage of tapping a proximal energy source.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Our conclusions are consistent with previous observations of a PMF requirement for flagellar growth from more than 25 years ago 19 , and extend the earlier findings in showing that export can be energized by PMF alone in the absence of any type III secretion ATPase 7 . Use of the proton gradient is perhaps not surprising given the speed of type III secretion and the likely advantage of tapping a proximal energy source.…”
supporting
confidence: 82%
“…The maintenance of normal ATP levels in the presence of CCCP was noted previously in experiments with Y. enterocolitica 7 and is thought to be due to a regulatory mechanism that inhibits the hydrolytic activity of the ATP synthase when the membrane is deenergized 10 . Because this protective mechanism may not act instantaneously, cellular ATP levels might undergo a transient drop following CCCP treatment that would escape detection in our measurements.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…As it has been shown that Yersinia enterocolitica type III secretion is inhibited considerably by treatment with the protonophore carbonyl cyanide m-chlorophenylhydrazone (CCCP) 22 , and that flagellar formation is also dependent on proton motive force (PMF) 23 , we investigated whether flagellar protein export is still dependent on PMF in the gain-of-function mutant as well as wild-type cells. The rate of cell growth decreased when CCCP concentration increased, Fig.…”
mentioning
confidence: 99%
“…InvC from S. enterica SPI-1 has been shown to unfold the exported proteins in an ATP-dependent manner and to detach some T3S substrates from their cytoplasmic chaperones before their export (Akeda and Galan, 2005). It is also probable that the ATPase energizes export but the proton motive force is also involved (Wilharm et al, 2004;Minamino and Namba, 2008;Paul et al, 2008). HrcN, the ATPase from P. syringae, forms hexamers and dodecamers that are activated by oligomerization and peripherally associated with the cytoplasmic side of the inner membrane (Pozidis et al, 2003).…”
Section: The Export Apparatusmentioning
confidence: 99%